ASSESSMENT LITERACY OF LECTURERS AND ITS IMPLEMENTATION IN THE INDONESIAN LANGUAGE AND LITERATURE EDUCATION STUDY PROGRAM - Zultiyanti (Universitas PGRI Palembang, 2025)
This study investigates the assessment literacy of PBSI (Indonesian Language and Literature Education) lecturers. It adopts a mixed-method approach, combining both descriptive quantitative and qualitative research designs. The research aims to evaluate the level of assessment literacy among PBSI lecturers in Indonesia, with a focus on how they implement assessment principles. The participants of the study were 20 PBSI lecturers, and data was gathered using a questionnaire. The data analysis process involved collecting and reviewing questionnaire responses, comparing these findings with expert opinions and existing studies related to lecturer assessment practices. The results revealed that PBSI lecturers possess good assessment literacy, as reflected in the 75% conformity rate across various indicators. Based on these findings, it is recommended that lecturers continue to improve their assessment practices while maintaining alignment with current educational standards. The study suggests further research to explore ways to enhance the overall effectiveness of assessment literacy among PBSI lecturers.